Case Study: Exploring the Structural Relationship of Teachers' Technological Pedagogical Content Knowledge in Learning and the Class XI Students’ Learning Outcomes - Santoso, Hajar Ahmad; Istiqomah, Nisa Rachmi (MATHEdunesa, 2025)
This research investigates the relationship between teachers' Technological Pedagogical Content Knowledge (TPACK) and class XI students’ learning outcomes, with a focus on factors that influence the effective integration of technology in teaching. Using a case study method with a qualitative and quantitative approach, this research involved five mathematics teachers and 100 students at SMAN 3 Sidoarjo. Data was collected through TPACK questionnaires, classroom observations, in-depth interviews, and student academic performance records. Analysis shows that higher levels of TPACK in teachers are positively correlated with improved student learning outcomes. Teachers with strong TPACK use technology effectively in their teaching, increasing student engagement and understanding. In addition, this research emphasizes the importance of collaboration with colleagues. Teachers who receive adequate training, resources, and technical support as well as collaborative support from colleagues are more successful in integrating technology into their teaching practices. These findings suggest that investing in ongoing professional development, providing strong administrative support, and creating a collaborative teaching environment are critical to improving student learning outcomes through technology.